Pemimpin dan Kepemimpinan - Hanantijo, GM. Djoko (Universitas Surakarta, 2010)
Abstract Leader that is success shall have some criterions which depend on viewpoint or approach applied, is that its the personality, skill, talent, its(the characters, or its(the authority owned is which later hardly having an effect on to theory and also leadership style which will be applied. Main secret of leadership is the biggest strength a leader is not from its the power, non its the intelligence, but from strength of its the person. a real leader striving improve; self repairs before business to improve; repair others. Hardly is required once leadership soul in each man person. The leadership soul needs always is fertilized and developed. At least to lead own self. Keyword: kepemimpinan, kekuasaan